Evaluation of Project P.A.T.H.S. (Secondary 2 Program) by the Program Participants: Findings Based on the Experimental Implementation Phase - Daniel T. L. Shek; Rachel C. F. Sun; Candace W. Y. Chan (The Scientific World Journal)
A total of 49 schools participated in the Secondary 2 Program of the Experimental Implementation Phase of the Project P.A.T.H.S. (Positive Adolescent Training through Holistic Social Programmes). After completion of the program, 7,406 students completed a Subjective Outcome Evaluation Form (Form A) designed by the research team to reveal their comments about the program, instructors, and perceived effectiveness of the program. Based on the consolidated reports submitted by the schools, the research team aggregated the data to form a “reconstructed” overall profile on the perceptions of the program participants. Results showed that high proportions of the respondents had positive perceptions of the program and the instructors. About 80% of the respondents were satisfied with the program and regarded it as helpful to their overall development. The present findings provide support to the effectiveness of Secondary 2 Program of Project P.A.T.H.S. from the perspective of the program participants.